Complexes of iron(II) with silylated pentalene ligands; building blocks for homo- and heterobimetallics - Kilpatrick, Alexander F.R.; Johnston, David R.; Green, Jennifer C.; Tsoureas, Nikolaos; Coles, Martyn P.; Cloke, F. Geoffrey N. (Polyhedron, 2016)
A range of iron(II) complexes incorporating the silylated pentalene ligands (Pn†H = 1,4-{SiiPr3}2C8H5and Pn† = 1,4-{SiiPr3}2C8H4) have been investigated as model molecules/building blocks for metallocene-based polymers. Six complexes have been synthesised and extensively characterised by a range of techniques, including by cyclic voltammetry and X-ray diffraction studies. Amongst these compounds are the homobimetallic [Cp∗Fe]2(μ-Pn†) which is a fused analogue of biferrocene, and the 3d/4s heterobimetallic [Cp∗Fe(η5-Pn†)][K] which forms an organometallic polymer in the solid state. DFT calculations on model mono-Fe(η5-Pn) compounds reveal the charge densities on the uncoordinated carbon atoms of the pentalene ligand, and hence the potential for incorporating these units into heteronuclear bimetallic complexes is assessed.
Keywords: Heterobimetallic; Homobimetallic; iron; Organometallic polymer; Pentalene